2007
DOI: 10.1590/s0102-76382007000300006
|View full text |Cite
|
Sign up to set email alerts
|

Ácido L-glutâmico na prevenção da calcificação de pericárdio bovino fixado em glutaraldeído: estudo em ratos

Abstract: RBCCV 44205-905Ácido L-glutâmico na prevenção da calcificação de pericárdio bovino fixado em glutaraldeído: estudo em ratos L-glutamic acid in the prevention of the calcification of bovine pericardial fixed in glutaraldehyde: study in rats Abstract Objective: To evaluate the efficiency of L-glutamic acid to prevent calcification of glutaraldehyde bovine pericardium implanted in rats' subcutaneous tissues.Methods: Fifty four Wistar rats were divided in six groups according to the type of the bovine pericardium … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 8 publications
0
5
0
Order By: Relevance
“…Treatment with glutamic acid reduced the amount of calcium in the control group, which had been documented by Ferreira et al [12]. Moreover, the study of Jorge-Herrero et al [8] glutamic acid was not as effective and, paradoxically, the pericardium treated behaved worse than the control group.…”
Section: Discussionmentioning
confidence: 82%
See 2 more Smart Citations
“…Treatment with glutamic acid reduced the amount of calcium in the control group, which had been documented by Ferreira et al [12]. Moreover, the study of Jorge-Herrero et al [8] glutamic acid was not as effective and, paradoxically, the pericardium treated behaved worse than the control group.…”
Section: Discussionmentioning
confidence: 82%
“…Preliminary study of our research group, using the same experimental model used here, has shown that glutamic acid was effective in reducing the calcification of bovine pericardium fixed in glutaraldehyde [12]. For this reason, fixed in glutaraldehyde bovine pericardium formed our control group, whereas the addition of decellularization or post-treatment were compared with glutamic acid alone or in combination to determine the most efficient way to reduce calcification.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Most studies used the implant model in TCSC of rats, which limits its interpretation because it does not assess the influence of bloodstream and tissue stress effects on calcification [12,13,15,16,21]. Our research group evaluated the effect of SDS decellularization in GDA-fixed bovine pericardium and implanted in the TCSC of rats for 90 days, with a reduction of 98% in the final amount of calcium (65.91 µg/mg tissue versus 1.24 µg/mg tissue) (unpublished data).…”
Section: Discussionmentioning
confidence: 99%
“…Several treatments were tested in order to eliminate or retard the calcification, but no method is quite effective yet [12][13][14][15][16]. The decellularization has been proposed as an alternative during the biological tissue processing of cardiovascular prostheses.…”
Section: Introductionmentioning
confidence: 99%